HOSPITAL STRATEGIC MANAGEMENT INNOVATION IN THE ERA OF HEALTH DIGITALIZATION: A LITERATURE STUDY - Sihotang, Oryza Sativa H.; Dilla, Nur Indah Rahma; Hutabarat, Husnida Putriyana; Anjaini, Nurul; Sembiring, Ayu Sukma Putri; Israyani, Israyani; Adelia, Nelsih; Mawarni, Dwiyana; Wasiyem, Wasiyem (Fakultas Ilmu Kesehatan, Universitas Ibn Khaldun, Bogor, 2025)
The development of digital technology has brought significant changes in the strategic management of hospitals, especially in efforts to improve the quality, efficiency and competitiveness of health services. This study aims to examine various strategic management innovations implemented by hospitals in Indonesia and globally in the era of health digitalization. This research was conducted using a systematic literature study method of 25 scientific articles published in the period 2022-2025. The results of the review show that the application of technologies such as Hospital Management Information System (SIMRS), digital marketing, telemedicine, and artificial intelligence has had a positive impact on operational effectiveness, data transparency, and patient experience. However, the digital transformation process is also faced with challenges such as limited infrastructure, resistance to change from human resources, and regulations that are not yet fully adaptive. Innovation-based management strategies, cross-sector collaboration, and strengthened governance are the keys to success in facing the dynamics of the digital era. This study recommends the importance of HR capacity building, digital infrastructure investment, and policy updates as strategic steps to support the sustainability of hospital management innovation in the future.